STUDYING AGGRESSIVE CLEARING BEHAVIOR OF DRIVERS AT UNCONTROLLED INTERSECTIONS UNDER MIXED TRAFFIC CONDITIONS - Kamalnath, Maddu; Dutta, Manish; Jena, Suprava (PREPARE@u® | IEI Conferences, 2021)
In this paper gap acceptance model and aggressive clearing model are developed for two uncontrolled 4-legged intersections in the state of Andhra Pradesh, India. Gap duration, type of major and minor road vehicles, speed of major road vehicle and clearing time are the parameters considered in this study which particularly reflects the driver’s clearing behaviour. This analysis showed that the probability of accepting a gap increases with increase in gap/lag value and decreases with increase in clearing time. It also decreases with increase in size of major road vehicle but increases with increase in size of minor road vehicle The level of aggressiveness of right turning vehicles increases with decrease in gap/lag and speed of major road vehicles, and it decreases with decrease in clearing time and size of minor road vehicles. Thus, in order to improve safety at uncontrolled intersections, measures such as minimization of side friction, installation of speed breakers on minor roads etc., should be followed which leads to faster movement of major road vehicles and thus lower the aggressiveness of drivers and increases safety.